A multi-element composite coated high nickel positive electrode material and preparation method thereof and lithium ion battery

By forming a cobalt-boron-antimony composite clad layer on the matrix of the high-nickel positive electrode material, and using dry ball mill mixing technology to achieve mechanical activation of the antimony source and boron source, the shortcomings of the high-nickel positive electrode material in terms of structure and interface stability are solved, and a low-residual lithium and high-performance battery material is achieved, which is suitable for large-scale industrial production.

CN119764426APending Publication Date: 2025-04-04HUNAN SHANSHAN ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510025995.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing high-nickel cathode materials have shortcomings in terms of structural and interface stability, resulting in a decline in battery performance. The traditional doping and coating modification strategies have problems such as complex process, high cost and difficulty in large-scale promotion.

Method used

Using multi-element composite coating technology, a cobalt-boron-antimony composite coating layer is formed on the surface of the high-nickel positive electrode material matrix, combined with dry ball milling mixing technology, the mechanical activation of the antimony source and the boron source is achieved, and a stable Li-B-O coating layer is formed to block the interaction between the active substance and the electrolyte.

Benefits of technology

High nickel cathode materials with low residual lithium, high first-term efficiency, high magnification and excellent circulation performance have been achieved, reducing the risk of thermal runaway in the battery, improving the safety of the battery and the feasibility of large-scale industrial production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764426A_ABST
    Figure CN119764426A_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of lithium-ion batteries, and discloses a multi-element composite coated high-nickel positive electrode material, including a high-nickel positive electrode material matrix and a cobalt-boron-antimony composite coating layer coated on the surface of the matrix. The preparation method thereof comprises: mixing a high-nickel positive electrode material precursor with a lithium source and an M'-containing compound, and then sintering the mixture under an oxygen atmosphere to obtain a doped high-nickel positive electrode material matrix; then mixing the mixture with a cobalt source, and then sintering the mixture under an oxygen atmosphere, and then dry-milling the mixture with a boron source and an antimony source to obtain the matrix. The present invention also discloses a lithium-ion battery comprising the multi-element composite coated high-nickel positive electrode material. The multi-element composite coated high-nickel positive electrode material of the present invention has the advantages of low residual lithium, high initial efficiency, high rate, excellent cycle performance, and high thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials, and in particular relates to a multi-element composite coated high-nickel positive electrode material and a preparation method thereof and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have been widely used in electric vehicles, portable electronic devices and energy storage systems. High-nickel cathode materials have become a very promising cathode material for lithium-ion batteries due to their high energy density and low cost advantages. However, due to interface problems caused by surface reconstruction and high residual lithium, and bulk problems caused by cation mixing, phase change and volume change, the structure and interface stability of high-nickel cathode materials still need to be improved. Generally, bulk doping and grain boundary coating can improve the performance of materials. However, the traditional dual modification strategy of doping and coating has problems such as complex process flow, high trial and error cost, and difficulty in large-scale application and promotion. Therefore, it is urgent to design a simple and efficient modification strategy to improve the performance of high-nickel cathode materials. The patent document with publication number CN111682174 A discloses an antimony-coated lithium battery positive electrode material and its preparation method and application. The patent first mixes the precursor with lithium hydroxide uniformly, obtains a monoalkyl matrix after the first high-temperature sintering, then washes and dries the monoalkyl matrix in deionized water to obtain a dry monoalkyl matrix, and then uniformly mixes and sinters the antimony source and the dry monoalkyl matrix to obtain an antimony-coated lithium battery positive electrode material. The patent uses water washing to remove residual lithium, which will inevitably destroy the surface structure of the material and promote the formation of NiO rock salt phase, and Li + / H proton exchange will reduce the active lithium content of the material, and ultimately significantly reduce the capacity, rate, and cycle performance of the material, resulting in increased impedance. The patent with announcement number CN110534717B discloses a method for coating a positive electrode material with LiMO2-B2O3, firstly, a lithium salt is uniformly mixed with a nickel cobalt manganese hydroxide precursor, and a lithium nickel cobalt manganese oxide matrix is ​​obtained after the first high-temperature sintering, and then it is ball-milled with a metal oxide and subjected to a second heat treatment to obtain a lithium nickel cobalt manganese coated matrix coated with a metal oxide film, and then mixed with a boron-containing compound and subjected to a third heat treatment to obtain a lithium nickel cobalt manganese positive electrode material coated with a metal oxide film and a LiMO2-B2O3 glassy composite coating film. In this patent document, the coating method adopts three sintering steps, which not only increases the cost in actual industrial production, but also cannot reduce the residual lithium of high-nickel materials, and therefore cannot reduce Li / Ni mixing and inhibit the formation of salt rock phase, thereby causing material structure degradation, and further affecting the performance of the battery, which is specifically manifested in O loss, Co dissolution and interface solvent decomposition, ultimately leading to a decrease in battery capacity, poor cycle performance, increased impedance, process problems and increased gas production. Summary of the invention

[0003] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology, and provide a multi-element composite-coated high-nickel cathode material with low residual lithium, high initial efficiency, high rate performance and excellent cycling performance, its preparation method and lithium-ion battery, and it is easy to be applied in large-scale industrial production.

[0004] To solve the above technical problem, the technical solution proposed by the present invention is as follows: A multi-element composite-coated high-nickel cathode material, comprising a high-nickel cathode material matrix and a cobalt-boron-antimony composite coating layer coated on the surface of the matrix.

[0005] Further preferably, the cobalt-boron-antimony composite coating layer includes various compounds of lithium, cobalt and oxygen (Li-Co-O), various compounds of lithium, boron and oxygen (Li-B-O) and Sb2O3.

[0006] For the above multi-element composite-coated high-nickel cathode material, preferably, the cobalt-boron-antimony composite coating layer is 0.6 wt% - 4 wt% of the mass of the matrix.

[0007] For the above multi-element composite-coated high-nickel cathode material, preferably, the mass of cobalt element in the cobalt-boron-antimony composite coating layer is 3000 - 20000 ppm of the mass of the matrix, the mass of boron element is 300 - 1000 ppm of the mass of the matrix, and the mass of antimony element is 300 - 1500 ppm of the mass of the matrix. For the above multi-element composite-coated high-nickel cathode material, preferably, the chemical formula of the high-nickel cathode material matrix is: Li a Ni x M y M’ z O2, where 1 ≤ a ≤ 1.1, 0.8 ≤ x < 1, 0 < y < 0.2, 0 < z < 0.2, x + y + z = 1; M is at least two of Co, Mn, Al, and M’ is selected from at least one of Mg, Sr, Nb, Ca elements.

[0008] Based on a general inventive concept, the present invention also provides a preparation method of the multi-element composite-coated high-nickel cathode material as described above, comprising the following steps: (1) Mix the high-nickel cathode material precursor with a lithium source and a compound containing M’, and then perform sintering treatment in an oxygen atmosphere to obtain a doped high-nickel cathode material matrix; (2) Mix the doped high-nickel cathode material matrix with a cobalt source, and then perform sintering in an oxygen atmosphere to obtain a cobalt-coated high-nickel cathode material; (3) Perform dry ball milling and mixing on the cobalt-coated high-nickel cathode material, a boron source and an antimony source to obtain the multi-element composite-coated high-nickel cathode material.

[0009] The chemical properties of the antimony source are stable and will not react with residual lithium. Therefore, in the conventional antimony coating process, water washing is required to remove residual lithium in advance. However, in this process, the nickel-rich positive electrode material will inevitably react when it comes into contact with water, and the Li + / H + Ion exchange makes the surface and near-surface of the material tend to delithiate, the inward migration of protons causes the layered material to shrink in the direction perpendicular to the transition metal and oxygen layer, and the outward migration of lithium reduces the electrochemically active lithium; in addition, the water washing process will also cause the surface of the positive electrode of the material to produce a salt rock phase with nanometer thickness and poor conductivity, thereby exacerbating the capacity and rate attenuation behavior during the cycle; and the antimony-containing coating layer will not provide a lithium ion transmission channel, and the sintering temperature should not be too high. Excessive sintering temperature will cause the antimony-containing compound to melt, which will inhibit the electrical properties of the material. The present invention adds an antimony source during the mechanical activation process of ball milling. The antimony source and the boron source complete the mechanical activation during the ball milling impact process, which not only does not require additional sintering, but also simultaneously realizes the moderate and uniform coating of the antimony source on the surface of the multi-element doped positive electrode material while the glassy viscous Li-BO is formed, which can more effectively block the interaction between the active substance and the electrolyte, thereby successfully preparing a modified high-nickel positive electrode material that can maintain high initial efficiency and high thermal stability.

[0010] In the above preparation method, preferably, in step (1), the sintering temperature is 720°C to 950°C, and the sintering holding time is 8 to 15 hours.

[0011] In the above preparation method, preferably, in step (2), the sintering temperature is 550°C to 750°C, and the sintering holding time is 3 to 10 hours. In the above preparation method, preferably, in step (3), the rotation speed of the ball mill is 300-600 rpm, and the ball milling time is 0.5-6 h.

[0012] In the above preparation method, preferably, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium acetate or lithium nitrate; The M'-containing compound is at least one of magnesium oxide, magnesium carbonate, magnesium oxalate, magnesium nitrate, hydrated magnesium nitrate, strontium oxide, strontium carbonate, strontium hydroxide, niobium trioxide, niobium pentoxide, calcium oxide or calcium carbonate; The cobalt source is at least one of cobalt hydroxide, cobalt oxide, cobalt trioxide or cobalt oxyhydroxide; The boron source is at least one of boron oxide, metaboric acid, and boric acid; The antimony source is at least one of antimony trioxide and antimony pentoxide.

[0013] In the above preparation method, preferably, the ratio of the lithium element in the lithium source to the transition metal element in the high-nickel positive electrode material precursor is 1.0-1.1:1; The mass of the cobalt element in the cobalt source is 3000-20000ppm of the mass of the doped high-nickel positive electrode material matrix; The mass of the boron element in the boron source is 300-1000ppm of the mass of the doped high-nickel positive electrode material matrix; The mass of the antimony element in the antimony source is 300-1500 ppm of the mass of the doped high-nickel positive electrode material matrix.

[0014] Based on a general inventive concept, the present invention also provides a lithium-ion battery, comprising the above-mentioned multi-element composite coated high-nickel positive electrode material or the multi-element composite coated high-nickel positive electrode material prepared by the above-mentioned preparation method.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The multi-element composite coated high nickel positive electrode material of the present invention has the advantages of low residual lithium, high initial efficiency, high rate, excellent cycle performance and high thermal stability.

[0016] (2) The present invention dopes elements into the matrix of high-nickel positive electrode materials. The doped elements can stabilize the bulk lattice, improve the lattice stability, and reduce the damage of bulk phase change to the structure; the cobalt-boron-antimony composite coating layer formed on the surface of the positive electrode material can not only consume residual lithium, but also be moderately and evenly distributed on the surface of the high-nickel positive electrode material. The coating layer has stable chemical properties and can effectively reduce the irreversible capacity loss of the ternary material during the cycle by inhibiting irreversible phase change and enhancing the electrochemical reversibility of the ternary material. It can also significantly inhibit the generation of electrode-electrolyte interface side reactions by avoiding direct contact between the electrolyte and the electrode surface, thereby effectively reducing the increase in interface impedance and charge transfer impedance. However, a single modification method has limited improvement on high-nickel positive electrode materials, and a single coating layer will gradually reduce HF corrosion resistance under high temperature, high voltage, and high current conditions, thereby leading to a decrease in cycle and rate performance. (3) In the preparation method of the present invention, cobalt coating is completed during the secondary heat treatment. This process consumes part of the residual lithium, which can significantly reduce the Li / Ni mixing and reduce the formation of salt rock phase, thereby achieving a stable material structure, thereby inhibiting O loss, Co dissolution and interface solvent decomposition, and ultimately increasing the battery capacity, improving high-temperature cycle performance and inhibiting gas production. Subsequently, the generated cobalt-coated high-nickel positive electrode material is dry-milled with a boron source and an antimony source. The boron source is easy to absorb water and has a low melting point. It can be self-wetting and adsorbed on the surface of the positive electrode material. Accompanied by the instantaneous impact heat generation during the ball milling process, the contact point will undergo mass transfer and diffusion driven by thermodynamics and concentration difference. The accumulated energy and heat can cause the boron source to undergo a mechanical activation reaction at room temperature, reacting with residual lithium to generate a Li-BO fast ion conductor. This process can not only continue to consume residual lithium, but also inhibit the decomposition of LiPF6 into HF. The generated Li-BO coating layer has high lithium ion conductivity and chemical stability, which can significantly increase the lithium ion diffusion rate, thereby effectively solving the problem of low initial efficiency of high-nickel positive electrode materials due to slow ion diffusion. In addition, the generated Li-BO also has faster lithium ion transport performance and lower charge transfer impedance, which can improve the reaction kinetics and rate performance of the electrode.

[0017] (4) In the present invention, an antimony source is added during the mechanical activation process of ball milling. The antimony source and the boron source are mechanically activated during the ball milling impact process, which not only does not require additional sintering, but also simultaneously realizes that the antimony source is moderately and evenly coated on the surface of the multi-element doped positive electrode material while the glassy viscous Li-BO is formed, which can further block the interaction between the active substance and the electrolyte, thereby successfully preparing a modified high-nickel positive electrode material that can maintain a high initial efficiency and has high thermal stability.

[0018] (5) The present invention utilizes the high stability of the antimony source to protect the positive electrode material. During the preparation process, there is no need to use a sintering process. Mechanical activation can be achieved through dry ball milling mixing, allowing the antimony source and Li-BO to be melted simultaneously and moderately and evenly on the surface of the high-nickel positive electrode material, repairing the gaps on the surface of the material and forming a moderately uniform surface coating layer. This can effectively reduce the penetration of the electrolyte, thereby inhibiting the generation of side reactions and significantly improving the high-temperature cycle performance of the material.

[0019] (6) The antimony source introduced in the present invention can also serve as an effective electronic conductor in the high-nickel positive electrode material, thereby improving the electrical conductivity of the material, which can help improve the charge and discharge efficiency and cycle stability of the battery; at the same time, the antimony source also exhibits excellent thermal stability and chemical stability. Under the high-temperature working environment of the battery, the addition of the antimony source can also effectively inhibit the insertion and extraction of lithium ions, thereby reducing the risk of thermal runaway of the battery and helping to improve the safety of the battery.

[0020] (7) The preparation method of the present invention omits the third sintering heat treatment process and adopts a dry process throughout the process, which greatly reduces the cost. It is simple and easy to operate, has low cost, and is easy to promote on a large scale. In particular, the third sintering is eliminated, which is suitable for most domestic factory production lines and completes the three-sintering to two-sintering process, making it suitable for large-scale production applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the multi-element composite coated high-nickel positive electrode material prepared in Example 1 of the present invention.

[0022] Figure 2 It is a residual lithium data diagram of the positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-4.

[0023] Figure 3 It is a graph of the DCR growth rate of the positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-4 after 50 cycles at 45°C. DETAILED DESCRIPTION

[0024] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0025] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0027] Embodiment 1: A multi-element composite coated high nickel positive electrode material of the present invention comprises a high nickel positive electrode material matrix LiNi 0.9468 Co 0.04 Mn 0.01 Sr 0.00089 Nb 0.00084 Ca 0.00147 O2 and a cobalt-boron-antimony composite coating layer coated on the surface of the substrate, the cobalt-boron-antimony composite coating layer is 0.88wt% of the substrate mass, the mass of the cobalt element in the cobalt-boron-antimony composite coating layer is 3000ppm of the substrate mass, the mass of the boron element is 500ppm of the substrate mass, and the mass of the antimony element is 1000ppm of the substrate mass. The method for preparing the multi-element composite coated high nickel positive electrode material in this embodiment comprises the following steps: (1) LiOH·H2O, Ni 0.95Co 0.04 Mn 0.01 The (OH)2 precursor, SrO, Nb2O5 and CaCO3 were mixed evenly according to the metal element molar ratio of 1.06:1:0.00089:0.00084:0.00147. The mixed raw materials were then heated from room temperature to 525°C in an oxygen atmosphere at a heating rate of 3°C / min for 2h, then heated to 750°C for 12h, and naturally cooled to room temperature to obtain LiNi 0.9468 Co 0.04 Mn 0.01 Sr 0.00089 Nb 0.00084 Ca 0.00147 O2 high nickel positive electrode material matrix.

[0028] (2) In LiNi 0.9468 Co 0.04 Mn 0.01 Sr 0.00089 Nb 0.00084 Ca 0.00147 CoOOH with a cobalt element mass of 3000ppm based on the mass of the matrix was added to the O2 high-nickel positive electrode material matrix. After being evenly mixed, the matrix was heated from room temperature to 625°C at a heating rate of 1°C / min in an oxygen atmosphere and calcined for 9h to obtain a cobalt-coated high-nickel positive electrode material.

[0029] (3) The cobalt-coated high-nickel positive electrode material, Sb2O3 with an antimony element of 1000 ppm of the matrix mass, and H3BO3 with a boron element of 500 ppm of the matrix mass were placed in a ball mill for ball milling at a speed of 300 rpm for 1.5 h to obtain a Li-Co-O / Li-BO / Sb2O3 multi-element composite coated high-nickel positive electrode material, whose SEM is as follows: Figure 1 As shown, the antimony source and Li-BO are synchronously and evenly melted on the surface of the high-nickel cathode material, repairing the cracks on the surface of the material and forming a moderately uniform and smooth surface coating layer.

[0030] Embodiment 2: The only difference between this embodiment and embodiment 1 is that the mass of the boron element in H3BO3 in step (3) is 1000 ppm of the mass of the matrix.

[0031] Embodiment 3: The present embodiment differs from embodiment 2 in that the Nb2O5 doping in step (1) is removed and the doping temperature in step (1) is changed from 750°C to 720°C.

[0032] Embodiment 4: The only difference between this embodiment and embodiment 1 is that the ball milling time in step (3) is 3 h.

[0033] Embodiment 5: The only difference between this embodiment and embodiment 2 is that the rotation speed of the ball mill in step (3) is 500 rpm.

[0034] Comparative Example 1: Compared with Example 1, in this comparative example, step (3) is not performed, and cobalt, boron and antimony are directly sintered and coated in step (2).

[0035] Comparative Example 2: The only difference between this comparative example and Example 1 is that no antimony source is added in step (3).

[0036] Comparative Example 3: The only difference between this comparative example and Example 1 is that no cobalt source is added in step (2).

[0037] Comparative Example 4: The difference between this comparative example and Example 1 is that in step (3), the mass of antimony element in Sb2O3 is 2000ppm of the mass of the matrix, and no boron source is added, and the rotation speed of the ball mill is 800rpm.

[0038] The residual lithium performance of the positive electrode materials prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-4 was tested. Specifically, 5 g of the high-nickel positive electrode material sample was accurately weighed into a 300 mL conical flask, 100 ml of deionized water was added, and the mixture was stirred on a magnetic stirrer for 5 minutes. After stirring, the solution was filtered with a quick filter paper into another 300 mL conical flask, and the original conical flask and filter paper were washed twice with deionized water; the filtrate was placed on a pre-set fully automatic potentiometric titrator for titration, and the titration endpoint was determined by monitoring the sudden change in the electrode potential. The residual lithium content in the sample was calculated based on the consumed titration volume and the concentration of the 0.1 mol / L HCL standard solution. The residual lithium performance data is shown in the figure below: Figure 2 As shown, in Comparative Example 1, the residual lithium is slightly higher because the boric acid is mainly decomposed into B2O3 at 625°C and does not continue to react with the residual lithium; in Comparative Example 2, since the antimony source and the residual lithium do not react, the values ​​are equivalent to those of Examples 1-4; Comparative Example 3 has a higher residual lithium due to the absence of a cobalt source to consume the residual lithium; in Comparative Example 4, no boron source is added to further consume the residual lithium to generate Li-BO, so the value is equivalent to that of Comparative Example 1.

[0039] The modified high-nickel cathode materials prepared in the above examples and comparative examples were assembled into button cells for electrochemical performance evaluation tests. Charge and discharge tests were conducted at 25°C, with a voltage range of 3.0-4.3V and a current density of 0.1C; rate performance tests were conducted at 25°C, with a voltage range of 3.0-4.3V and a current density of 2C; and high-temperature cycle performance tests were conducted at 45°C, with a voltage range of 3.0-4.3V and a current density of 0.5C. The results are shown in Table 1. The DCR growth rate of 50 cycles at 45°C is shown in the figure. Figure 3 shown.

[0040] Table 1 Buckling performance of modified high nickel positive electrode materials prepared in various embodiments and comparative examples

[0041] In Comparative Example 1, since cobalt, boron and antimony are coated in one step, the sintering temperature of boric acid is too high and decomposes into boron oxide, which neither reacts with the remaining residual lithium nor promotes the transmission of lithium ions, and does not form a moderately uniform lithium-containing coating layer, which is not conducive to capacity, rate and cycle performance; in addition, at too high a temperature, the antimony-containing compound will be excessively melted, thereby coating the surface of the material more completely, and excessive coating will hinder the transmission of lithium ions during the charging and discharging process of the material, which is not conducive to the capacity and the first effect. Therefore, Comparative Example 1 is worse than Example 1 in capacity, rate and cycle performance to varying degrees. From the comparison between Example 1 and Comparative Example 2, it can be seen that since an antimony source is introduced in Example 1, and the antimony-containing coating layer has stable chemical properties and is not easy to participate in the reaction during the charging and discharging process, it can ensure that the coating layer remains intact during multiple cycles, which helps to reduce the new contact surface of the material during the charging and discharging process, thereby inhibiting the side reactions caused by the contact between the electrolyte and the material, and improving the material cycle stability. From the comparison between Example 1 and Comparative Example 3, it can be seen that since no cobalt source is added in Comparative Example 3, part of the residual lithium cannot be consumed, the Li / Ni mixing cannot be reduced, and the formation of the salt rock phase cannot be reduced, so the structure of the material cannot be stabilized, and further, the loss of O, the dissolution of Co, and the decomposition of the interfacial solvent cannot be suppressed, which ultimately reduces the battery capacity, deteriorates the high-temperature cycle performance, and increases the gas production. From the comparison between Example 1 and Comparative Example 4, it can be seen that since the amount of antimony source coating in Comparative Example 4 is too much and no boron source is added, the coating layer is too thick, which affects the conductivity and is not conducive to the electrochemical performance, and the ball milling speed is too fast, which will cause the particles to be severely broken and the temperature is too high, thereby affecting the properties of the coating layer. The above multiple aspects cause the electrochemical performance of the material to be adversely affected.

[0042] The embodiments 1-4 of the present invention stabilize the bulk structure by selecting appropriate elements for doping, and significantly reduce the residual lithium through the cobalt coating, which can not only increase the capacity but also repair the surface defects of the material; mechanical activation is achieved by dry ball milling mixing, so that the antimony source and Li-BO are synchronously and evenly melted on the surface of the high-nickel positive electrode material, further repairing the gaps on the surface of the material, forming a moderately uniform surface coating, effectively reducing the penetration of the electrolyte, thereby inhibiting the generation of side reactions, and significantly improving the high-temperature cycle performance of the material. Among them, the addition of a boron source can further consume residual lithium, improve kinetic performance, and improve the rate performance of the material; further adding an antimony source with high conductivity, excellent thermal stability and chemical stability can further improve the charge and discharge efficiency, thermal stability and cycle stability of the battery. As a result, suitable doping and multi-element coatings play a synergistic role to effectively improve the electrochemical properties of the material. The prepared material as shown in Example 1 has a discharge capacity of 224.2 mAh / g at 0.1C and a discharge rate of 93.5% at 2C. Even after 50 cycles at a high temperature of 45°C, the capacity retention rate is still as high as 94.7%, and the cycle DCR growth rate is 20.3%. Compared with Comparative Examples 1-4, its electrochemical performance is greatly improved.

[0043] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A multi-element composite coated high nickel positive electrode material, characterized in that: It includes a high-nickel positive electrode material substrate and a cobalt-boron-antimony composite coating layer coated on the surface of the substrate.

2. The multi-element composite coated high nickel positive electrode material according to claim 1, characterized in that: The cobalt-boron-antimony composite coating layer accounts for 0.6wt% to 4wt% of the mass of the substrate.

3. The multi-element composite coated high nickel positive electrode material according to claim 1, characterized in that: The mass of the cobalt element in the cobalt-boron-antimony composite coating layer is 3000-20000 ppm of the mass of the substrate, the mass of the boron element is 300-1000 ppm of the mass of the substrate, and the mass of the antimony element is 300-1500 ppm of the mass of the substrate.

4. The multi-element composite coated high nickel positive electrode material according to claim 1, characterized in that: The chemical formula of the high-nickel cathode material matrix is: Li a Ni x M y M’ z O2, where 1 ≤ a ≤ 1.1, 0.8 ≤ x < 1, 0 < y < 0.2, 0 < z < 0.2, and x + y + z = 1; M is at least two of Co, Mn, and Al, and M’ is selected from at least one of the elements Mg, Sr, Nb, and Ca.

5. A method for preparing a multi-element composite coated high nickel positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing a high nickel cathode material precursor with a lithium source and an M'-containing compound, and then sintering the mixture in an oxygen atmosphere to obtain a doped high nickel cathode material matrix; (2) mixing the doped high-nickel cathode material matrix with a cobalt source, and then sintering the mixture in an oxygen atmosphere to obtain a cobalt-coated high-nickel cathode material; (3) The cobalt-coated high-nickel positive electrode material is mixed with a boron source and an antimony source by dry ball milling to obtain the multi-element composite-coated high-nickel positive electrode material.

6. The preparation method according to claim 5, characterized in that: In step (1), the sintering temperature is 720°C to 950°C, and the sintering holding time is 8 to 15 hours; In step (2), the sintering temperature is 550°C to 750°C, and the sintering holding time is 3 to 10 hours.

7. The preparation method according to claim 5, characterized in that: In step (3), the rotation speed of the ball mill is 300-600 rpm, and the ball milling time is 0.5-6 h.

8. The preparation method according to claim 5, characterized in that: The lithium source is at least one of lithium hydroxide, lithium carbonate, lithium acetate or lithium nitrate; The M'-containing compound is at least one of magnesium oxide, magnesium carbonate, magnesium oxalate, magnesium nitrate, hydrated magnesium nitrate, strontium oxide, strontium carbonate, strontium hydroxide, niobium trioxide, niobium pentoxide, calcium oxide or calcium carbonate; The cobalt source is at least one of cobalt hydroxide, cobalt oxide, cobalt trioxide or cobalt oxyhydroxide; The boron source is at least one of boron oxide, metaboric acid, and boric acid; The antimony source is at least one of antimony trioxide and antimony pentoxide.

9. The preparation method according to claim 5, characterized in that: The ratio of the lithium element in the lithium source to the transition metal element in the high-nickel positive electrode material precursor is 1.0-1.1:1; The mass of the cobalt element in the cobalt source is 3000-20000ppm of the mass of the doped high-nickel positive electrode material matrix; The mass of the boron element in the boron source is 300-1000ppm of the mass of the doped high-nickel positive electrode material matrix; The mass of the antimony element in the antimony source is 300-1500 ppm of the mass of the doped high-nickel positive electrode material matrix.

10. A lithium ion battery, characterized in that: It comprises the multi-element composite coated high-nickel positive electrode material as described in any one of claims 1 to 4, or comprises the multi-element composite coated high-nickel positive electrode material prepared by the preparation method as described in any one of claims 5 to 9.

Citation Information

Patent Citations

  • Cathode materials and their preparation methods

    CN110534717B

  • Antimony-coated lithium battery positive electrode material and preparation method and application thereof

    CN111682174A